Requalificação de espaços livres ao longo do igarapé da Beira Rio, entre os bairros do Coroado e do Aleixo, Manaus-AM - Queiroz, Isabel Ferreira (Brasil, 2024)
With the accelerated population growth since the creation of the Zona Franca in 1967, there was deforestation of green areas in Manaus, resulting in one of the least wooded municipalities in the country (IBGE, 2010). With this, the objective of this work is to requalify the space on the banks of the Igarapé Beira Rio, from the source within the APA Floresta Manaós to its outlet in the Igarapé do Mindu, including the stretch from the Praça do Conjunto Petros to Campo do Soldado (Coroado). With a descriptive and explanatory research, a territorial analysis of the area and research of successful case studies (for analysis of solutions and applied technologies), a proposal was elaborated for the requalification of the banks of the igarapé with a linear park, maintaining at the same existing uses to the maximum, proposing the recovery of the water quality of the igarapé, complementing the riparian forest with the use of native species and encouraging the proximity of the population to the igarapé.